LOSS OF MITOCHONDRIAL AMINO ACID CATABOLISM METABOLISM WITH AGE DRIVES REPRODUCTIVE SENESCENCE. (11th November 2018) - Curran, S; Yen, C
Abstract: The contribution of normal cellular metabolism on sperm health and function are not well-defined. Here we show that changes in mitochondrial homeostasis in response to defective mitochondrial proline catabolism has direct roles in maintaining distinct aspects of sperm quality and competitive fitness. Disruption of alh-6, which facilitates the second step of proline catabolism by converting P5C to glutamate, results in premature reproductive senescence, specifically in males. The generation and accumulation of the toxic P5C metabolic intermediate drives oxidative stress, changes in mitochondrial morphology and depletion of energy storing metabolites in sperm, which impair male sperm competitive advantage. Surprisingly the germline phenotypes in response to alh-6 loss are not influenced by diet, as opposed to the somatic homeostasis that can be restored in a diet-dependent manner. Taken together, our results define a role for mitochondrial proline catabolism on sperm function and reveal the importance mitophagy on male reproductive health.